Bloating and gas formation: modern opportunities for treatment - L. I. Butorova; N. G. Kadnikova; M. A. Osadchuk; T. E. Plavnik; G. M. Tokmulina (Лечащий Врач, 2021)
Bloating is a subjective feeling of excessive gas formation and passage of gasses. It is more common in patients with gastrointestinal disorders. For therapy of disorders involving excessive gas formation, fermentative nutraceutical containing alpha-galactosidase can be applied,. Alpha-galactosidase provides fermentative activity which is absent in human body, and prevents entrance of complex sugars to the large intestine in non-split form.